Karacadağ weaving traditions: a brief overview of the Türkan people - Aksoy, Elif (Routledge Journals, Taylor & Francis Ltd, 2025)
Originally nomadic in Central Asia, the T & uuml;rkan people now reside in settled villages within the Karacada & gbreve; region of eastern Anatolia, approximately ten-hour drive from the Turkish capital, Ankara. Renowned for their weaving and textile arts, these communities maintain traditional practices that have endured with minimal influence from modern technological advancements. This study is based on fieldwork conducted in various villages of Karacada & gbreve; between 11 and 17 June 2020. In addition to direct observations, the researcher used a questionnaire distributed among local weavers to gather insights into their hand-weaving techniques. The paper presents the findings of this survey, accompanied by photographs illustrating the techniques, colours, and patterns characteristic of the region's handcrafted textiles.
Keywords: East Anatolia; Karacada & gbreve;; T & uuml;rkan; intercultural exchange; weaving; bridewealth